The Therapeutic Strategies for Eliminating Biofilm Produced by Staphylococcus Aureus Isolated from Catheter by Exposing to Radiation Emitted from Radioactive Sources (In Vitro) - Mohammed, Nebras Rada; Ali, Noor (Generasi Sains Indonesia, 2024)
This study aimed to evaluate the effectiveness of Sr90 radiation in eliminating biofilm production and inhibiting the growth of Staphylococcus aureus, a Gram-positive, facultative anaerobic bacterium responsible for infections such as pneumonia, sepsis, and bacteremia, whose virulence is enhanced by biofilm formation. A cross-sectional descriptive design combined with a case–control analytical approach was employed, with bacterial isolates obtained from catheters and other clinical samples of patients in Baghdad hospitals during 2023–2024. Biofilm-producing S. aureus isolates were exposed to varying doses of Sr90 radiation, with and without aluminum shielding, and their biofilm activity was assessed using Congo-Red Agar before and after exposure. Results demonstrated that all isolates (100%) exhibited biofilm production prior to treatment; however, after exposure to Sr90, biofilm production was completely inhibited (0%), as indicated by red colony coloration on Congo-Red Agar. Furthermore, Sr90 exposure produced 100% bactericidal activity across increasing doses and time intervals, whether aluminum shielding was applied or not. These findings provide evidence that Sr90 radiation effectively disrupts biofilm production and eradicates S. aureus, highlighting its potential as an innovative therapeutic strategy for managing biofilm-associated infections.